Green Lemons - Environmental Labels and Entry into an Environmentally Differentiated Market under Asymmetric Information - Michael Kuhn (Universität Rostock, Institut für Volkswirtschaftslehre, 1999)
The paper inquires whether a public eco-label mitigatesadverse selection, where an ecologically superior (green) product variant is underprovided. A model, integrating entry into a perfectly competitive, vertically differentiated industry and rationally expected quality structure (REQS) under asymmetric information, provides conditions for the label, serving as screening device, to increase green supply and curb pooling. Perverse reactions entail decreasing green supply, enhanced pooling, or increasing non-green supply. It is shown that the common single crossing property disregards the impact of changes in REQS on absolute profitability and may misdiagnose firms' incentives to attain the label. if labelling causes market expansion, pollution may increase even if substitution towards the green variant occurs. However, this only happens if both variants are environmentally sensitive in a well-defined sense.
Keywords: L11; L15; Q28; 330; asymmetric information; eco-labelling; entry; market structure; screening; vertical dif-ferentiation; Produktqualität; Umweltzeichen; Markteintritt; Asymmetrische Information; Produktdifferenzierung; Marktstruktur; Theorie